2019
DOI: 10.3390/molecules24122343
|View full text |Cite
|
Sign up to set email alerts
|

Duodenoscope-Associated Infections beyond the Elevator Channel: Alternative Causes for Difficult Reprocessing

Abstract: Objectives: Duodenoscopes have been widely used for both diagnostic and therapeutic endoscopic retrograde cholangiopancreatography (ERCP) procedures, but recently, numerous outbreaks of multidrug-resistant organisms (MDRO) infections have been reported which has led to extensive research for their possible causes. Consequently, the aim of this study is to search for possible duodenoscope surface damages that could provide an alternative and plausible source of infections. Materials and Methods: In order to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…The recording of the heat flow as a function of temperature induced composition-dependent transitions in, but not limited to polymer-based structures, playing a very important role in elucidating different material aging behaviors (microbiological, thermal, photochemical, etc.) [ 22 , 23 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The recording of the heat flow as a function of temperature induced composition-dependent transitions in, but not limited to polymer-based structures, playing a very important role in elucidating different material aging behaviors (microbiological, thermal, photochemical, etc.) [ 22 , 23 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study95 concluded that CO 2 emissions associated with single-use scopes is 24–47 times that of reusable scopes, with manufacturing accounting for over 90% of the greenhouse gas emissions. In this specific context, the use of disposable elevator caps might be a more sustainable alternative to disposable complete duodenoscopes95–98 and is recommended for further evaluation by national bodies 99. A reduction in transmissible infections after ERCP may therefore be achieved by innovations to endoscope design, optimising decontamination and reprocessing100 as well as adoption of quality assurance measures 77.…”
Section: Methodsmentioning
confidence: 99%
“…Mehrere Eigenschaften wie das Design und der komplexe Aufbau flexibler Endoskope wurden als mögliche Risikofaktoren definiert, die zur Übertragung beitragen könnten [4,6,7]. Auch eine verzögerte oder unzureichende Trocknung vor der Lagerung und eine nicht strikte Einhaltung der Aufbereitungsvorschriften wurden als Risikofaktoren identifiziert [1].…”
Section: Zusammenfassungunclassified